Cost-effectiveness analysis of olaparib as maintenance therapy in patients with platinum-sensitive relapsed ovarian cancer and a BRCA1/2 mutation in china - Shu, Yamin; Liu, Yanxin; He, Xucheng; Ding, Yufeng; Zhang, Qilin (Frontiers in Pharmacology, 2022)
Objective: The aim of this study was to investigate the cost-effectiveness of olaparib as the maintenance therapy in patients with platinum-sensitive relapsed ovarian cancer and a BRCA1/2 mutation in China. Methods: A Markov model was developed to simulate the clinical course of typical patients with ovarian cancer in the SOLO2 trial. Weibull survival model was employed to fit the Kaplan-Meier progression-free survival and overall survival probabilities of the olaparib and placebo strategy, respectively. The clinical and direct costs data were derived from randomized clinical trials and published reports. Quality-adjusted life-years (QALYs) and incremental cost-effectiveness ratios (ICER) were estimated over a 10-year lifetime horizon. Meanwhile, one-way and probabilistic sensitivity analyses were used to explore the impact of uncertainty on the model’s outcomes. Results: Overall, the incremental effectiveness and cost of olaparib versus placebo were 0.56 QALYs and $43,292.92, resulting in an ICER of $77,620.56/QALY, higher than the willingness-to-pay (WTP) threshold of China ($31,498.70/QALY). The results were sensitive to the cost of olaparib and utility of PFS. Scenario analyses suggested that when the cost of olaparib was reduced by 60%, ICER decreased to $30,611.52/QALY lower than the WTP threshold of China. Conclusion: The findings from the present analysis suggest that olaparib with the cost 60% discount as maintenance therapy might be cost-effective in patients with platinum-sensitive relapsed ovarian cancer and a BRCA1/2 mutation in China.